2021
DOI: 10.1101/2021.09.28.462237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of Blos1 by IRE1 prevents the accumulation of Huntingtin protein aggregates

Abstract: Huntington's Disease is characterized by accumulation of the aggregation-prone mutant Huntingtin (mHTT) protein. Here, we show that expression of mHTT in mouse cultured cells activates IRE1, the transmembrane sensor of stress in the endoplasmic reticulum, leading to degradation of the Blos1 mRNA and repositioning of lysosomes and late endosomes toward the microtubule organizing center. Overriding Blos1 degradation results in accumulation of larger mHTT aggregates and increased cell death. Although mHTT is degr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Retrograde trafficking helps the localization of aggregated proteins to the microtubule organizing center (MTOC) and disruption in trafficking hinders the degradation of these aggregates. A very recent preprint found how degradation of Blos1 mRNA via IRE1 mediated process influences mHtt degradation prior to the formation of large aggregates [ 62 ]. Bae et al showed the retrograde trafficking and clustering of lysosomes and late endosomes (LEs) near the MTOC is induced by the IRE1.…”
Section: Er Stress Proteins and Their Involvement In Hd Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Retrograde trafficking helps the localization of aggregated proteins to the microtubule organizing center (MTOC) and disruption in trafficking hinders the degradation of these aggregates. A very recent preprint found how degradation of Blos1 mRNA via IRE1 mediated process influences mHtt degradation prior to the formation of large aggregates [ 62 ]. Bae et al showed the retrograde trafficking and clustering of lysosomes and late endosomes (LEs) near the MTOC is induced by the IRE1.…”
Section: Er Stress Proteins and Their Involvement In Hd Pathologymentioning
confidence: 99%
“…However, prior to formation of larger aggregates, mHTT is degraded via an ESCRT (endosomal sorting complex required for transport)-dependent, endosomal microautophagy pathway. This pathway is controlled by Blos1 degradation and appears to protect cells from a toxic, less aggregated form of mHTT [ 62 ].…”
Section: Er Stress Proteins and Their Involvement In Hd Pathologymentioning
confidence: 99%